Rancang Bangun Alat Pemilah Biji Kopi Berdasarkan Kualitas Buah Menggunakan Sensor TCS3200 - Pratama, bayu rizki; sembiring, jaka persada (Department of Electrical Engineering, Faculty of Engineering, Universitas Lampung, 2024)
Coffee fruit is a trade commodity that has been known for centuries. Coffee fruit can be processed into a delicious drink, but when coffee farmers harvest at the same time, farmers combine immature and ripe coffee fruit in one container, this results in a decrease in the quality of the taste. significant. In this research, the fuzzy Sugeno method was used to determine the classification of ripe, semi-ripe and ripe coffee fruit. This tool uses an Arduino Uno Atmega328 microcontroller to control the TCS3200 color sensor as a reader for the color of the coffee fruit and uses a servo to sort the coffee fruit according to quality. In testing the automatic control system for separating coffee beans based on color using the TCS3200 Color Sensor, it was successful in directing the coffee beans to a predetermined container. Keywords— TCS3200 Sensor, Arduino ATmega328P,Coffee,Color,Quality,Fuzzy sugeno.